(untitled) (Palimpsesto, 2023)
The article analyzes the pedagogical strategies of inclusion exercised by lead teachers in the educational community, from the stories of five teachers from municipal schools in the city of Talca, in Chile. The research question is: What pedagogical strategies of inclusion do head teachers use to articulate an educational community with the presence of immigrant students? It is suggested as a hypothesis that teachers use professional, institutional and experiential pedagogical strategies. The research —guided by a synthetic theoretical approach—is based on the multiple case study method, considering each teacher who works with foreign students as a case study. The research concludes that, although the head teachers value the inclusion of diversity to favor an intercultural educational community, their practices respond more to pedagogical strategies of cultural intermediation than to inclusion procedures. This fact reports a gap in initial teacher training to deal with culturally diverse educational communities.